Exploring Leadership in the Hybrid Workplace - Ebojoh, Sandra; Högberg, Karin (International Journal of Advanced Corporate Learning (iJAC), 2024)
The workplace and work life has changed due to advances in digital technology, which has increased distributed work. Many organizations no longer work in a physical office, but in a hybrid workplace where organizational members work both remotely, using digital technology, and in the physical office. This literature review explores and examines the existing research on leadership in hybrid workplaces. While there is a large body of research on e-leadership and numerous studies on the pandemic, there is a paucity of research on the leadership of hybrid workplaces, which is crucial in the present workplace. Hence, this paper is a systematic review of the literature that addresses leadership in the hybrid workplace across disciplines. A total of 48 papers from six databases were analyzed and interpreted. This review reveals the different but complementary disciplinary focus contributing to developing the knowledge of leadership in the hybrid workplace. It also presents a comprehensive overview of changes to the workplace and the critical challenges leaders face with the abrupt switch to the new structure of the workplace. This work has significant learning points for leadership practice in the contemporary workplace. It offers a conceptualization of hybrid leadership, along with propositions for future research.